Curve Characteristics and Foraminal Dimensions in Patients With Adult Scoliosis and Radiculopathy. Issue 2 (March 2017) - Pugely, Andrew J.; Ries, Zachary; Gnanapragasam, Gnanapradeep; Gao, Yubo; Nash, Rachel; Mendoza-Lattes, Sergio A.
Abstract : Study Design: Retrospective cohort study. Objective: To demonstrate a correlation between radiculopathy symptoms, foraminal morphology, and curve types. Summary of Background Data: Patients with degenerative scoliosis frequently present with foraminal stenosis and radiculopathy, the origin of which is not well understood. Methods: A total of 48 patients (384 foraminas) were included: 14 with low back pain (B); 16 with femoral nerve pain (F); and 18 with sciatic nerve pain (S). The symptomatic foramen of groups F and S were compared with asymptomatic foramina. Alignment was measured from standardized radiographs; 3D-CT reconstructions were used to measure foraminal height and area. Data are presented as mean±SD. The χ 2, t test, and Pearson coefficients were calculated; as well as interobserver and intraobserver reproducibility (Cohen κ). Results: Seventeen of the 18 patients with sciatic nerve pain (S) presented foraminal stenosis (<40 mm 2 ) at the concavity of the fractional curve distal to the main lumbar structural curve. The symptomatic foramina were significantly smaller in height (7.8±2.5 vs. 12.1±3.1 mm, P <0.0001) and area (30.1±14.3 vs. 57.6±28.7 mm 2, P <0.0001) compared with asymptomatic foramen; 7/7 patients with femoral nerve pain (F) and lumbar structural curves (apex L3 or lower) had foraminal stenosis at the concavity of the fractional curve. Eight of the 9 patients with femoral nerve pain (F) and thoracic, thoracolumbar, or lumbar (apex L2 or higher) curves, presented foraminal stenosis in the concavity of the caudal fractional curve. The symptomatic foraminal spaces were significantly smaller in height (9.2±3.2 vs. 12.1±3.1 mm, P <0.0001) and area (30.1±15.2 vs. 57.6±28.7 mm 2, P <0.0001). Foraminal height correlated with foraminal area ( r =0.68–0.85; P <0.0001). Interobserver agreement was between 0.6092 and 0.8679. Conclusions: A correlation between curve types and symptomatic foraminal stenosis exists. Adult scoliosis patients with sciatic nerve pain typically present with foraminal stenosis at the concavity of the caudal fractional curve. Similarly, patients with femoral nerve pain present with foraminal stenosis at the concavity of the caudal fractional curve when the main structural curve is thoracic, thoracolumbar, or lumbar (apex L2 or higher).